The informatics pathway for hospital infection quality control monitoring - Wang, Hui; Huang, Qin; Tian, Qingqing; Yang, Weiwei; Liu, Anran; Tang, Jiayang; Zhang, Hailin; Wu, Chunlin (Frontiers in Public Health, 2025)
ObjectiveTo analyze the results and current status of hospital infection monitoring and quality control work at a tertiary specialized cancer hospital, providing references for further improvement of HAI monitoring quality.MethodsCombined information-based monitoring with manual quality control measures for hospital infection surveillance, collecting data such as hospital infection report cards and missed reports to analyze the current status of hospital infection monitoring. Starting from January 2023, further comprehensive quality control measures were taken, and data before and after the implementation were compared to evaluate the effectiveness of the quality control work.ResultsAfter the implementation of comprehensive management measures, the incidence rate of hospital infection in the hospital decreased from 0.60 to 0.52%, the correct rate of early warning disposal increased from 85.31 to 89.53%, and the handling rate within 24 h of early warning increased from 20.51 to 72.99%. All these differences are statistically significant (p < 0.05). After the comprehensive management measures were adopted, more missed cases were detected and reported, resulting in an increase in the missed reporting rate from 5.36 to 12.33% (p < 0.05). While the number of reports increased, the accuracy of the reports decreased from 67.54 to 54.05% (p < 0.05).ConclusionInformation systems can enhance the efficiency of hospital infection surveillance through real-time monitoring and automatic early warning, improve the quality of reporting, and thereby contribute to the reduction of the incidence rate of hospital infections. However, the quality of monitoring is still influenced by human factors such as whether the early warning rules are scientifically set and whether the determination of hospital infections is accurate. There may be situations where the missed reporting rate is underestimated and the quality of the report cards is not high. This indicates that while adopting information-based monitoring, we cannot ignore the management of quality control. It is necessary to continuously strengthen the investigation of missed reporting, improve the quality of report cards, and ensure the authenticity and accuracy of the results of hospital infection monitoring.